Quantification of impact of lime on mechanical behaviour of lime cement blended mortars for bedding joints in masonry systems - Ramesh, Meera (2019)
In the case of blended lime-cement mortars used for bedding joints in masonry systems, substitution of cement with lime in the binder involves changes in strength and stiffness. However, extensive quantification and correlation of these changes in mechanical properties appear to be scarcely explored in existing literature. This work aims at providing a methodical experimental campaign, targeting 14 different lime-cement mixes with the quantity of lime in the binder varying from 10% to 75% (by volume), binder-aggregate (B/Ag) ratios – of 1:3, 1:4, 1:5 and 1:6 at 6 different curing ages from 7 to 180 days. Changes in compressive strength and flexural strength were expressed as functions (equations) of lime content in the binder, B/Ag ratio and curing age. Every 1% increment in the quantity of lime in the binder led to approximately 1.4% decrease in mechanical strength of the mortar with respect to the reference (10% lime in the binder). Furthermore, correlation(s) between ultrasound pulse velocity (UPV), density, compressive and flexural strength have also been explored. Compressive strength divided by flexural strength provided an almost constant value for all lime-cement compositions at all ages (ratio ∼ 3), decreasing as a function of B/Ag ratio in the mix. The work has been concluded with a discussion on trends in E-modulus (4–18 GPa) and open porosity (23%–27%) as a function of lime content in the binder of the mix and the age of the mortar.